TINJAUAN HUKUM INTERNASIONAL ATAS SERANGAN MILITER AMERIKA SERIKAT TERHADAP ISLAMIC STATE OF IRAQ AND SYRIA DI WILAYAH NEGARA IRAK DAN SURIAH - Rizky Irfano Aditya; Siti Muslimah (Faculty of Law Universitas Sebelas Maret, 2016)
This research aims to determine International law view on theUnited States military agression against Islamic State of Iraq and Syria in the territory of Iraq and Syria.This research is a normative research viewed from prescriptive with statute and case approach. This research is using primary legal materials and secondary legal materials. The legal materials collected through library research and study of the document which is then analyzed using a technique based on the method of deductive reasoning deduction. The result shows that U.S. military agression against Islamic State of Iraq and Syria in the territory of Iraq and Syria never violates international law. Intervention, which practically is prohibited because its capability of violating state’s sovereignity gets its legitimation by several conditions. Responsibility to Protect principle which concerns on human rights establishment also bridges intervention and state’s sovereignity principle.